Inside the football factory: young players` reflections on being `released` - Gorman, J.; Blackwood, L. (Qualitative Research in Sport, Exercise and Health, 2025)
Every year, most young football players experience deselection and for some, this has profound consequences including drug addiction and death. Yet little is known about these young hopefuls whose careers are abruptly cut short and who are released into a world they are ill prepared for. This study brings a social psychological lens to examine how social identity processes underpin these consequences. Our research sheds light on the formation of a footballer identity in young players; one that is exclusive and excluding, that devalues alternative identities, and that cuts young players off from alternative sources of self-worth and support. The first author, a deselected player with professional football experience, conducted semi-structured interviews with eight males (M = 26.63, SD = 4.66), who had been deselected at an early age. Through reflexive thematic analysis we identified three themes that spoke to (a) the centrality of football identities and how this was fostered by clubs to the detriment of players; (b) the experience of deselection as `exiting the bubble` and the mixed emotions of pain, relief, and bewilderment; and (c) the enduring importance and complex understanding of the footballer identity as something that continues to shape who they are. Our analysis implicates players, their parents, clubs, and wider society in the development of a footballer identity, which leaves young men vulnerable to life-long health consequences. Our findings contribute to calls for deeper consideration and action around football club culture, and clubs` responsibility for player welfare, including when players are released.